Resentment of Kenyan Colonial Chiefs : Why Colonial Era Chiefs in Kenya Were Highly Resented - Irungu, Stephen (IJRDO - Journal of Social Science and Humanities Research, 2020)
The current essay reviews the reasons why local communities highly resented the colonial era chiefs. It offers the background of the chief rule in Kenya, wherein some communities such as the Agikuyu people had few chiefs as a council of elders ruled them. To such communities, the concept of chief administration was alien, influencing their opposition to colonial administration that used chiefs to administer to the local communities. To ensure the main cases for the colonial-era chief resentment by locals are understood, the essay utilizes the cases of five chiefs that include Nabongo wa Mumia, Njiiri wa Karanja, Lenana wa Laibon, Waruhiu wa Kung’u and Nindo who were senior chiefs under the colonial governments. Through their cases, the essay shows how their implementation of colonial rule contributed to the local community hating them as they were viewed as the traitors of their community. Most of the chiefs used as cases in the current essay were also hated as they pursued personal richness rather than using their leadership position to uplift the welfare of their communities. They also engaged in the recruitment of community members who were used in forced labor and the forceful recruitment of young men to fight in the first and second world war leading to an increase in resentment among the local communities.